PEMBENTUKAN KARAKTER DAN IDENTITAS BANGSA MELALUI PENDIDIKAN MULTIKULTURAL - Minahul Mubin; Maskuri Bakri (LPPM Institut Agama Islam Al-Hikmah Tuban, 2021)
In the world of education, the negative impacts caused by the industrial revolution 4.0, ranging from radicalism, discrimination, cultural fading local, criminal acts from social media and the real world resulting from a lack of understanding of multicultural education. Changes that occur from technology and information, economics, socio-culture, and education demand to be able to adapt to change. So that efforts are needed to improve multicultural education, which is based on the character and values ​​that reflect the identity of the Indonesian nation so that it can go hand in hand with technological sophistication, wisdom, taste and a strong nationalist spirit. This research method uses a qualitative method with a library research approach. The results of this study are, by inculcating life values ​​which are a reflection of the character and national identity of the Indonesian nation which is a reflection of national identity, resulting in religious attitudes, honesty, tolerance, discipline, creative, independent, democratic, national spirit, love for the homeland , and be responsible. Keywords: Character Building, National Identity, Multicultural Education